2020
DOI: 10.1007/s10554-020-01855-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiography-based quantitative coronary contrast-flow ratio measurements correlate with myocardial ischemia assessed by stress MRI

Abstract: Contrast-flow quantitative flow ratio (cQFR) is a new technology for quantitative evaluation of coronary stenosis using computational fluid dynamics based on angiograms. The aim of this study was to assess the sensitivity and specificity of cQFR to detect myocardial ischemia using stress magnetic resonance imaging (MRI) as a reference standard. Patients who received stress MRI and coronary angiography were selected from the hospital database. Relevant ischemia on stress MRI was defined as a perfusion deficit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A comprehensive cardiac magnetic resonance imaging (CMR) examination was performed, including steady-state free precession cine sequences, T1 and T2 mapping, T2STIR (T2 weighted imaging with short tau inversion recovery), early and late gadolinium enhancement (LGE) using a T1 weighted fast gradient-echo sequence with adjusted inversion recovery pre-pulse as well as phase-sensitive inversion recovery sequence, on a 3.0-T scanner (Achieva, Philips Medical System, Best, The Netherlands) with a 32-channel phased-array surface coil with dS anterior and posterior coil. A standardized protocol was used as described earlier 12 . Cine images were acquired covering the entire left ventricle in contiguous short axis and long axis using a steady-state free precession sequence (slice thickness 8 mm, no interslice gap).…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive cardiac magnetic resonance imaging (CMR) examination was performed, including steady-state free precession cine sequences, T1 and T2 mapping, T2STIR (T2 weighted imaging with short tau inversion recovery), early and late gadolinium enhancement (LGE) using a T1 weighted fast gradient-echo sequence with adjusted inversion recovery pre-pulse as well as phase-sensitive inversion recovery sequence, on a 3.0-T scanner (Achieva, Philips Medical System, Best, The Netherlands) with a 32-channel phased-array surface coil with dS anterior and posterior coil. A standardized protocol was used as described earlier 12 . Cine images were acquired covering the entire left ventricle in contiguous short axis and long axis using a steady-state free precession sequence (slice thickness 8 mm, no interslice gap).…”
Section: Methodsmentioning
confidence: 99%
“…So far, only a limited number of studies compared the diagnostic accuracy of QFR with non-invasive myocardial perfusion imaging modalities, achieving in part discordant results. Lenk et al recently revealed a high association between QFR and myocardial ischemia assessed by stress CMR with a diagnostic accuracy of 86% [ 14 ]. In line with these observations, Smit et al showed an overall accuracy of 90% of QFR in the detection of myocardial ischemia on single-photon emission computed tomography myocardial perfusion imaging (SPECT) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we and others could demonstrate in large retrospective studies that QFR may be effectively used to evaluate the presence of ischemia in non-culprit lesions in the context of acute coronary syndromes [ 9 , 10 , 11 , 12 ]. QFR also shows a good concordance with stenosis geometry [ 13 ] and with non-invasive detection of ischemia, although the latter is less extensively explored [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, QFR demonstrated a higher diagnostic value for determining FFR-defined, lesion-specific ischemia compared to SPECT and PET. Lenk et al 33) revealed that coronary stenosis calculated by QFR is highly correlated with ischemic areas detected by stress magnetic resonance imaging (MRI).…”
Section: Comparison With Other Modality For Myocardial Ischemia Evaluationmentioning
confidence: 99%